Efficacy and Safety of Long‐Term Baricitinib With and Without Methotrexate for the Treatment of Rheumatoid Arthritis: Experience With Baricitinib Monotherapy Continuation or After Switching From Methotrexate Monotherapy or Baricitinib Plus Methotrexate. Issue 8 (29th July 2020) - Fleischmann, Roy; Takeuchi, Tsutomu; Schiff, Michael; Schlichting, Douglas; Xie, Li; Issa, Maher; Stoykov, Ivaylo; Lisse, Jeffrey; Martinez‐Osuna, Pindaro; Rooney, Terence; Zerbini, Cristiano A. F.
Abstract : Objective: To evaluate the long‐term efficacy and safety of maintaining baricitinib monotherapy in patients with active rheumatoid arthritis (RA) originally treated with baricitinib monotherapy or switched from methotrexate (MTX) or the combination of baricitinib plus MTX to baricitinib monotherapy. Methods: This is a post hoc analysis of patients from the RA‐BEGIN study who entered a long‐term extension, RA‐BEYOND, and were assessed for up to 24 weeks. In RA‐BEGIN, MTX‐naive patients with early active RA were randomized to MTX monotherapy, baricitinib 4 mg monotherapy, or baricitinib 4 mg plus MTX. At week 52, all patients entering RA‐BEYOND received baricitinib 4 mg monotherapy. MTX could be prescribed during RA‐BEYOND at the investigator's discretion. Results: Patients in RA‐BEYOND who were not rescued in RA‐BEGIN (n = 423) were evaluated. Of these, 47% continued baricitinib monotherapy and 53% added MTX, with similar proportions from the 3 original arms. Patients with lower disease activity at the RA‐BEYOND baseline generally continued to do well with baricitinib monotherapy as assessed by the Simplified Disease Activity Index, the Clinical Disease Activity Index, and the Health Assessment Questionnaire disability index scores. Patients prescribed MTX had higher disease activity at the RA‐BEYOND baseline and had improved disease activity after the addition of MTX. Safety outcomes were similar across treatment groups. Conclusion: Many patients responded well to continued baricitinib monotherapy or to switching to baricitinib monotherapy from MTX monotherapy or baricitinib plus MTX, showing sustained or improved disease control. The groups of patients who had less disease control on their original therapies showed sustained or improved disease control with the addition of MTX to baricitinib.